The reductive catalytic upcycling of polyolefin plastic waste - Alessandro Piovano; Emilia Paone (Current Research in Green and Sustainable Chemistry, 2022)
Plastics, and polyolefins (POs) in particular, revolutionized the everyday life, and after use the waste accumulation is raising severe environmental concerns fostering an intense the research towards more sustainable and profitable recycling routes.In this contribution, we focus the attention concerning recent advances on the reductive upgrading of POs promoted by heterogeneous catalysts, that is emerging as a valid alternative to pyrolysis since POs are transformed into valuable chemicals and fuels, allowing overcome the issue of elevated temperatures, as well as low selectivity and fast catalyst deactivation. As a matter of fact, the introduction of H2 gas in the reactor allows to carry out PO degradation in milder conditions coupled with a higher control on the produced hydrocarbons, depending on the employed catalyst and the reaction parameters. Two main processes have been so far developed: hydrogenolysis and hydrocracking, respectively leading to formation of diesel and gasoline. At a molecular level, their difference relies on the different typologies of catalysts, which are monofunctional metal catalysts in the former case (where both surface hydrides and surface alkyl species are formed and recombine each other), and bifunctional acid/metal catalysts in the latter (where, after a carbocation is formed by protonation, the reaction proceeds by isomerization and scission). Despite the conceptually simple and univocal definition of the two mechanisms, several catalytic processes have been developed in the last years, varying for both reaction conditions and obtained products, thus generating a quite complex scenario.Hereafter, the most significant results are reported to provide a consistent base for further progress.